Rewiring the Central Metabolic Pathway for High‐Yield l‐Serine Production in Corynebacterium glutamicum by Using Glucose. Issue 6 (20th May 2019) - Zhang, Xiaomei; Lai, Lianhe; Xu, Guoqiang; Zhang, Xiaojuan; Shi, Jinsong; Koffas, Mattheos A. G.; Xu, Zhenghong
Abstract : l ‐Serine is widely used in the pharmaceutical, food,  and cosmetic industries. The direct fermentative production ofl ‐serine from glucose in Corynebacterium glutamicum ( C. glutamicum ) has been achieved but the yield is generally low. In this study, the central metabolic pathway is rewired to direct higher accumulation of glycerate‐3‐phosphate (3‐PG), the precursor forl ‐serine biosynthesis, thereby freeing up more carbon to enhancel ‐serine production and yield. To this end, the native phosphotransferase system (PTS) is inactivated by deleting the gene ptsH. Meanwhile, the PTS‐independent glucose uptake pathway is activated via overexpression of iolT1, ppgk, and deletion of the transcriptional regulator gene iolR . Furthermore, metabolic changes between PTS and non‐PTS strains are elucidated using gas chromatography–tandem mass spectrometry. Based on the metabonomic and enzyme activities analysis, the glycolysis pathway upstream of 3‐PG is further enhanced by co‐overexpressing pgi, pfkA, and gapA . The resulting strain with all of the modifications mentioned above leads to thel ‐serine yield of 0.30 g g −1 glucose (42.8% higher than that of the original strain), which is the highest yield in C. glutamicum by using glucose as the sole carbon source. These strategies can be expanded for the production of other value‐added chemicals derived from the intermediates of glycolysis pathway in C. glutamicum . Abstract : l ‐Serine is widely used in the pharmaceutical, food, and cosmetic industries. In this study, the central metabolic pathway is rewired for high‐yieldl ‐serine production in Corynebacterium glutamicum ( C. glutamicum ) by using glucose. These strategies can be expanded for the production of other value‐added chemicals derived from the intermediates of glycolysis pathway in C. glutamicum . This article is part of an AFOB (Asian Federation of Biotechnology) Special issue. To learn more about the AFOB visit www.afob.org.